Evolving Body Contouring Strategies for Patients After Massive Weight Loss: Insights from Bariatric and Pharmacologic Interventions - Giordano, Salvatore; Salval, Andre'; di Summa, Pietro; Oranges, Carlo Maria (MDPI AG, 2025)
Background/Objectives: Significant weight loss, whether through bariatric surgery or medication-assisted approaches, presents unique challenges for body contouring procedures. A thorough preoperative evaluation is essential to optimize outcomes and minimize risks. Methods: A comprehensive literature search was conducted across various databases to identify studies on assessment, nutritional optimization, thromboembolic risk, and surgical planning for post-weight-loss patients, with a particular focus on those undergoing medication-assisted weight loss using Glucagon-like peptide-1 (GLP-1) agonists. Results: A detailed review of medical history, comorbidities, weight loss trajectory, and nutritional status is essential. Common conditions such as diabetes, hypertension, and sleep apnea often improve after weight loss but require ongoing management. Nutritional deficiencies, particularly in vitamins and minerals, necessitate dietary counseling and supplementation. Patients who have undergone significant weight loss are at increased risk of thromboembolic events, particularly after body contouring procedures. Surgical planning should be patient-centered, setting realistic expectations and employing a strategic, staged approach when necessary to optimize outcomes. GLP-1 agonists users require special consideration due to their distinct metabolic and physiological profiles. Conclusions: Optimizing preoperative assessment, nutrition, and thromboprophylaxis is critical for safe and effective body contouring in post-weight-loss patients. With the increasing prevalence of medication-assisted weight loss, surgical strategies must adapt to address the distinct anatomical and physiological features of these patients.